Increasing Autopsy Rates at a Public Hospital - Souza, Victor L (Blackwell Science Inc, 1997)
Despite the acknowledged value of autopsies, autopsy rates are low in American hospitals. We developed an extensive intervention to increase the autopsy rate on the medical service of our urban teaching hospital and to identify obstacles to obtaining permission for autopsy. The 6-month intervention increased the autopsy rate from 7.5% during the previous 2 years to 16.8%, but this effect disappeared after the intervention. Among patients for whom permission for autopsy was not obtained, physicians failed to request permission for 31% and families refused permission for 69%.